Chemoresistance in Breast Cancer Patients Associated With Changes in P2X7 and A2A Purinergic Receptors in CD8+ T Lymphocytes - Ruiz-Rodríguez, Victor Manuel; Turiján-Espinoza, Eneida; Guel-Pañola, Jaime Arturo; García-Hernández, Mariana Haydee; Zermeño-Nava, José de Jesús; López-López, Nallely; Bernal-Silva, Sofia; Layseca-Espinosa, Esther; Fuentes-Pananá, Ezequiel M.; Estrada-Sánchez, Ana María; Portales-Pérez, Diana Patricia (Frontiers in Pharmacology, 2020)
Breast cancer is the most frequent cancer type that afflicts women. Unfortunately, despite all the current therapeutic strategies, many patients develop chemoresistance hampering the efficacy of treatment. Hence, an early indicator of therapy efficacy might aid in the search for better treatment and patient survival. Although emerging evidence indicates a key role of the purinergic receptors P2X7 and A2A in cancer, less is known about their involvement in breast cancer's chemoresistance. In this sense, as the chemotherapeutic treatment stimulates immune system response, we evaluated the expression and function of P2X7 and A2A receptors in CD8+ T cells before and four months after breast cancer patients received neoadjuvant chemotherapy. The results showed an increase in the levels of expression of P2X7 and a decrease in the expression of A2A in CD8+ T cells in non-chemoresistant (N-CHR) patients, compared to chemoresistant (CHR) patients. Interestingly, in CHR patients, reduced expression of P2X7 occurs along with a decrease in the CD62L shedding and the production of IFN-γ. In the case of the A2A function, the inhibition of IFN-γ production was not observed after chemotherapy in CHR patients. A possible relationship between the modulation of the expression and function of the P2X7 and A2A receptors was found, according to the molecular subtypes, where the patients that were triple-negative and human epidermal growth factor receptor 2 (HER2)-enriched presented more alterations. Comorbidities such as overweight/obesity and type 2 diabetes mellitus (T2DM) participate in the abnormalities detected. Our results demonstrate the importance of purinergic signaling in CD8+ T cells during chemoresistance, and it could be considered to implement personalized therapeutic strategies.